Grain Quality of Wheat Genotype Dewata Grown Under Wet Tropical Climate of Indonesia - Muhammad Ikhsan Sulaiman; Irman Syahroni; Rita Andini; Lukman Hakim (Agroindustrial Journal, 2020)
Along with prosperity improvement of countries in the tropic, the consumption of wheat-based pro ducts such as breads, cakes, noodles and cookies has increasing tendency in the recent years. Wh eat that is grown usually in the sub-tropic has been investigated intensively for trial cultivation in tropical region. Successful cultivation of wheat in the tropic has been reported but the informatio n on its quality was still very few. This paper reported the quality of wheat grown in the field expe riment at 5 different provinces of Indonesia at an altitude ranged from 1000 up to 1650 meter abo ve sea level. Two samples of wheat from each location were taken and analyzed the physical, che mical, pasting and dough properties. The quality of wheat genotype Dewata was varied dependin g on the planting location. Out of five planting locations, only Jawa Tengah could produce good q uality of wheat. Meanwhile, the wheat from other locations were characterized by weak in pasting and dough properties. Wheat with weak pasting and dough properties could not be used for brea d and noodles’ production. However, they were still suitable to produce cookies and cake